2020
DOI: 10.31234/osf.io/z9qke
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep and Next-Day Negative Affect and Suicidal Ideation in Borderline Personality Disorder

Abstract: Sleep disturbance is associated with elevated suicidal ideation and negative affect. To date, however, no study has investigated the temporal relationship between sleep and suicidality among those diagnosed with borderline personality disorder (BPD). This preregistered (https://osf.io/4vugk) study tested whether nightly sleep (self-reported sleep duration, sleep onset latency, and subjective leep quality) represents a (within-person) short-term risk factor for affective dysregulation and increases in suicide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Most reports failed to establish independent temporal predictors of suicidal ideation severity: of twelve articles fitting temporal prediction models (47, 51, 52, 55-57, 60, 73, 74, 76, 77), four failed to establish significant predictors after accounting for ideation at the previous time point (47,52,55), and five did not control for prior ideation (51,60,73,74,76). Across studies, prior suicidal ideation therefore remained the strongest (or only) predictor of subsequent ideation (i.e., suicidal ideation at T significantly predicting ideation at T+1).…”
Section: Prediction Of Stbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports failed to establish independent temporal predictors of suicidal ideation severity: of twelve articles fitting temporal prediction models (47, 51, 52, 55-57, 60, 73, 74, 76, 77), four failed to establish significant predictors after accounting for ideation at the previous time point (47,52,55), and five did not control for prior ideation (51,60,73,74,76). Across studies, prior suicidal ideation therefore remained the strongest (or only) predictor of subsequent ideation (i.e., suicidal ideation at T significantly predicting ideation at T+1).…”
Section: Prediction Of Stbsmentioning
confidence: 99%
“…One study indicated that active coping reduced the intensity of ideation at the subsequent assessment 2 h later (77). Between days, short sleep duration (both objective and subjective), poor subjective sleep quality and increased sleep latency (i.e., time to fall asleep) predicted (mean) next-day suicidal ideation (51,74). Negative interpersonal events were also associated with increased next-day suicidal ideation (73).…”
Section: Prediction Of Stbsmentioning
confidence: 99%